Ibn Ṭufayl’s Ḥayy ibn Yaqẓān: An Almohad Reading - Fierro, Maribel (Islam and Christian-Muslim relations, 2020)
Ibn Ṭufayl’s (d. 581/1185) connection with Almohad rulers and involvement in the Almohad doctrinal and intellectual project has been addressed by Nemesio Morata and Lawrence Conrad, among others. Conrad argues that Ibn Ṭufayl belonged to the newly created Almohad elites, the ṭalaba, the empire’s doctrinarians. Morata analyses the famous passage where Ibn Ṭufayl presents Ibn Rushd al-Ḥafīd (Averroes) to the then prince Abū Yaʿqūb Yūsuf - who would become the second Almohad caliph (r. 558/1163-580/1184) - when the young philosopher was commissioned to write his commentaries on Aristotle. Ibn Ṭufayl’s Risālat Ḥayy b. Yaqẓān has, however, rarely been analysed in the Almohad context in which it was written, despite being one of the earliest works written under Almohad rule. Here I propose precisely such a reading of the text, showing Sufism, philosophy and politics as inextricably linked. This proposal, with its specific identification of the two main characters of the Risāla, Ḥayy and Absāl, considers the needs that the new polity had at the time to develop a post-Messianic orientation that would preserve the loyalty of the first followers (Berber-speaking tribesmen from the Maghrib), while attracting the urbanized Andalusis and, more importantly, their scholarly elites.